Influence of loading and use of occlusal splint in implant-supported fixed prostheses - Teixeira, Fabíola Marchezini; De Assis Claro, Cristiane Aparecida; Neves, Ana Christina Claro; De Mello Rode, Sigmar; Da Silva-Concílio, Laís Regiane (Wolters Kluwer, 2012)
The aim of the study was to assess the tensions generated in the long axis of the implants and the interimplants in the cervical, middle, and apical regions when subjected to different loads with or without interposition of the flat occlusal plane splint. A photoelastic model was made with 2 external hexagon implants located in the space corresponding to the second premolar and molar inferiors. A screw-retained metal superstructure was installed on the implants with a torque of 20 NIcm, and the set (photoelastic model with superstructure) were positioned in the circular polariscope in the dark-field configuration to observe the distribution of isochromatic fringes around the implants and interimplant areas. Photographic records were obtained before the application of the occlusal load with the following loading conditions: 300, 600, and 900 N, with and without interposition of the occlusal plane splint. The decrease in stress with the application of the flat occlusal plane splint became more evident after the application of the 600-N load. Generally, the major stress magnitude occurred in the cervical region for interimplant areas and in the apical region around implants. Use of occlusal splint in the loading of 300, 600, and 900 N reduced tension 33.22%, 66.66%, and 73.33%, respectively, in the samples. It can be concluded that the interposition of the occlusal plane splint caused a reduction in tension resulting from the simulation of occlusal overload. Copyright © 2012 by Mutaz B. Habal, MD.
Keywords: Bruxism; Dental implant; Fixed partial dentures; Photoelastic stress analysis